Estimating of times and Heliospheric Location of the accelerated energetic protons associated with two CMEs in the Multi Eruption Solar Energetic Particle (MESEPs) events - Al-Feadh, D. (University of Thi-Qar Journal of Science, 2014)
We have selected two Multi Eruption Solar Energetic Particle (MESEP) events among 268 MESEP events during the solar cycle 23 observed by Energetic and Relativistic Nuclei and Electron (ERNE) instrument on board Solar and Heliospheric Observatory (SOHO) with intensities of >10-3 cm-2 sr-1 s-1 MeV-1 at energies (1-116) MeV . We have estimated the time and place of the acceleration for the energetic protons injected by two Coronal Mass Ejection (CMEs) associated with each MESEP event. We have calculated the injection time of the energetic protons by using the fixed path length and the Velocity Dispersion Analysis (VDA) methods, assuming that particles with different energies were released simultaneously at the Sun. We found that in both methods the bulk of the acceleration occur during the impulsive phase near the Sun.